General concepts of decision support system for the needs of agrochemical enterprises of Russian Federation; Молодежь и современные информационные технологии; Ч. 2 - Markov A. V.; Pertsev A. V.; Sherstnev V. S. Vladislav Stanislavovich; Morozov V. S. Vasiliy Sergeevich (Геоинформационные системы)
Заглавие с титульного экрана